Disparate viral pandemics from COVID19 to monkeypox and beyond: a simple, effective and universal therapeutic approach hiding in plain sight - Johnson, Howard M.; Ahmed, Chulbul M. (Frontiers in Immunology, 2023)
The field of antiviral therapeutics is fixated on COVID19 and rightly so as the fatalities at the height of the pandemic in the United States were almost 1,000,000 in a twelve month period spanning parts of 2020/2021. A coronavirus called SARS-CoV2 is the causative virus.Development of a vaccine through molecular biology approaches with mRNA as the inducer of virus spike protein has played a major role in driving down mortality and morbidity. Antivirals have been of marginal value in established infections at the level of hospitalization. Thus, the current focus is on early symptomatic infection of about the first five days. The Pfizer drug paxlovid which is composed of nirmatrelvir, a peptidomimetic protease inhibitor of SARS-CoV2Mpro enzyme, and ritonavir to retard degradation of nirmatrelvir, is the current FDA recommended treatment of early COVID19. There is no evidence of broad antiviral activity of paxlovid against other diverse viruses such as the influenza virus, poxviruses, as well as a host of respiratory viruses. Although type I interferons (IFNs) are effective against SARS-CoV2 in cell cultures and in early COVID19 infections, they have not been broadly recommended as therapeutics for COVID19. We have developed stable peptidomimetics of both types I and II IFNs based on our noncanonical model of IFN signaling involving the C-terminus of the IFNs.We have also identified two members of intracellular checkpoint inhibitors called suppressors of cytokine signaling (SOCS), SOCS1 and SOCS3 (SOCS1/3), and shown that they are virus induced intrinsic virulence proteins with activity against IFN signaling enzymes JAK2 and TYK2. We developed a peptidomimetic antagonist, based on JAK2 activation loop, against SOCS1/3 and showed that it synergizes with the IFN mimetics for potent broad spectrum antiviral activity without the toxicity of intact IFN molecules. IFN mimetics and the SOCS1/3 antagonist should have an advantage over currently used antivirals in terms of safety and potency against a broad spectrum of viruses.